Kajian Pegunungan Meratus Sebagai Geopark Nasional - M. Arief Anwar; Gusti Syahrani Noor; Wajidi; Ahmad Zaky Maulana; Yudhi Putryanda; Dewi Siska (Jurnal Kebijakan Pembangunan, 2018)
One of South Kalimantan's development priorities is South Kalimantan to one of the national tourism destinations, and in an effort to glorify the earth's heritage for the welfare of the people, the Provincial Government of South Kalimantan plans to make the meratus mountains become national geopark. Therefore it is deemed necessary to conduct a study related to the Geopark development plan. As a first step to realize this, an initial study of the development of mountains meratus as a national geopark was carried out. The objectives of this study are (1) Identifying the mountainous area (Geosite) which has the potential to be developed by national geopark, (2) Analyzing the location conditions of the area (Geosite) referred to in relation to be developed as a national geopark and (3) Establishing policy recommendations / strategies what needs to be taken in the development of the national geo park of the Meratus mountain region.The analytical method used is (1) descriptive qualitative analysis to describe the mountainous Meratus area that will be used as a geopark (2) a spatial analysis to map which meratus mountain area will be used as a geopark area. The results show that in general there are 57 geosite points that have the potential to be developed as part of the Meratus mountain geopark. The theme that can be raised in this geopark meratus is the meratus geopark as the ofiolite Mountains, considering that in the Meratus mountain range it is composed of the oldest rocks which form the depositional base of all rocks in the South Kalimantan region and also one of the oldest rocks exposed in Indonesia. Abstrak Salah satu prioritas pembangunan Kalimantan Selatan adalah mewujudkan Kalsel sebagai salah satu destinasi wisata nasional, dan dalam upaya memuliakan warisan bumi untuk kesejahteraan masyarakat, Pemerintah Provinsi Kalimantan Selatan berencana menjadikan pegunungan meratus sebagai Geopark Nasional. Oleh karena itu dipandang perlu melakukan suatu kajian terkait rencana pengembangan Geopark tersebut. Sebagai langkah awal untuk merealisasikan hal tersebut maka penting dilakukan studi awal pengembanganpegunungan meratus sebagai geopark nasional. Tujuan dari kajian ini adalah (Mengidentifikasi kawasan Geosite pegunungan meratus yang memiliki potensi untuk dikembangkan geopark nasional, ( Menganalisis kondisi lokasi kawasan Geosite dimaksud dalam kaitannya untukdikembangkan sebagai geopark nasional dan ( Menetapkan rekomendasi/strategi kebijakan yang perlu diambil dalam pengembangan geopark nasional kawasan Pegunungan Meratus. Metode analisis yang digunakan adalah ( analisis kualitatif deskriptif untuk menggambarkan kawasan pegunungan meratus yang akan dijadikan geopark ( analisis spasial untuk menentukan titik titik lokasi kawasan pegununganmeratus yang akan dijadikan kawasan geopark Hasil kajian menunjukan secara umum terdapat 57 titik geosite yang berpotensi dikembangkan sebagai bagian dari geopark pegunungan meratus. Penelitian ini menyimpulkan bahwa konsep tematik yang diangkat adalah geopark Meratus sebagai Pegunungan ofiolit mengingat pada pegunungan Meratus tersusun oleh batuan tertua yang menjadi dasar pengendapan dari semua batuan yang ada di wilayah Kalimantan Selatan dan juga menjadi salah sat u batuan tertua yang ada di Indonesia.